Financial Report Analysis Based On Liquidity, Profitability, Solvency, And Activity Ratio PT. Mitra Adiperkasa Tbk Period 2022-2023 - Ramadhan, Yanuar; Josephin Cornellius; Yani Ariwibowo; Herman Prasetyo; Widy Maulana Iqbal (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research aims to analyze the financial performance of PT. Mitra Adiperkasa Tbk during the 2022-2023 period uses liquidity, profitability, solvency, and activity ratios. The data used are company financial reports obtained from existing websites. The analysis results show that the company's liquidity ratio experienced a slight decline during the research period, but was still above the average industry standard. The company's profitability ratio fluctuates, with a decrease in 2022 and a slight increase in 2023. The company's solvency ratio shows a healthy and stable financial condition, with a slight increase during the research period. The company's activity ratio shows a stable trend, with a slight decline in 2023. Overall, the financial performance of PT. Mitra Adiperkasa Tbk during the 2022-2023 period is considered quite good. The company has sufficient ability to meet its short-term obligations but needs to increase its profitability. The company has a healthy and stable financial condition and can manage its assets efficiently.